THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE AND CREATIVITY ON THE ENTREPRENEURIAL INTEREST OF TWELFTH GRADE STUDENTS AT UPT SMA NEGERI 3 SIDENRENG RAPPANG - HASNADIA RUSDY; MUHAMMAD JUFRI, ASMAYANTI, AGUS SYAM, SUMIATI TAHIR (CV. Adiba Aisha Amira, 2026)
The purpose of this study was to determine the effect of entrepreneurial knowledge and creativity on entrepreneurial interest in class XII students of SMA Negeri 3 Sidenreng Rappang. The independent variables in this study are entrepreneurial knowledge and creativity while the dependent variable is entrepreneurial interest. The population in this study were all class XII students of SMA Negeri 3 Sidenreng Rappang for the period of 289 students. While the sample in this study was 75 respondents using random sampling technique. Data collection was carried out by distributing a list of questions (questionnaires) to respondents. The data analysis technique used was multiple linear regression analysis using SPSS software. Based on the results of the analysis and discussion, it can be concluded that: The Entrepreneurial Knowledge variable (X1) partially influences the dependent variable, namely Entrepreneurial Interest (Y). Furthermore, the Creativity variable has a partial effect on the dependent variable, namely Entrepreneurial Interest (Y). The Entrepreneurial Knowledge variable (X1) and Creativity (X2) simultaneously influence the dependent variable, Interest in entrepreneurship (Y)